PENGARUH PEMBERIAN TABLET FE DENGAN SARI KACANG HIJAU TERHADAP PENINGKATAN HB PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS DUNGALIYO - Harismayanti Harismayanti; Fahmi A. Lihu; Wirta Kasmat Umar (Universitas Muhammadiyah Gorontalo, 2020)
Anemia is the most severe level of iron deficiency and occurs when hemoglobin (Hb) concentrations are far below the threshold determined as anemia. One of the greatest causes of maternal death is anemia or iron (Fe) deficiency. Has been found one way to deal with nutritional anemia, especially in pregnant women, is through supplementing Fe tablets and increasing the intake of Fe food sources, green bean extract. This research was conducted in Dungaliyo Health Center. The purpose of this study was to identify the effect of giving Fe tablets and green bean extract to increase hemoglobin (Hb) level in pregnant women. The researcher used quasi experimental design with two group pre-test - post test. Samples were 34 pregnant women who were taken by using total sampling techniques. This research instrument was a Hb measurement questionnaire. Statistical tests using T-t test dependent on the increase in Hb in pregnant women before and after the intervention with level of significancy 0,000 (p-value < 0,05). The result showed that there is an effect of giving Fe tablets with green bean extract to increase hemoglobin in women at Dungaliyo Community Health Center.